A roadmap for enabling Industry 4.0 by artificial intelligence - Chatterjee, Jyotir Moy; Garg, Harish; Thakur, R. N. (Hoboken, NJ : Wiley ; Beverly, MA : Scrivener Publishing, 2023)
A ROADMAP FOR ENABLING INDUSTRY 4.0 BY ARTIFICAIAL INTELLIGENCE The book presents comprehensive and up-to-date technological solutions to the main aspects regarding the applications of artificial intelligence to Industry 4.0. The industry 4.0 vision has been discussed for quite a while and the enabling technologies are now mature enough to turn this vision into a grand reality sooner rather than later. The fourth industrial revolution, or Industry 4.0, involves the infusion of technology-enabled deeper and decisive automation into manufacturing processes and activities. Several information and communication technologies (ICT) are being integrated and used towards attaining manufacturing process acceleration and augmentation. This book explores and educates the recent advancements in blockchain technology, artificial intelligence, supply chains in manufacturing, cryptocurrencies, and their crucial impact on realizing the Industry 4.0 goals. The book thus provides a conceptual framework and roadmap for decision-makers for implementing this transformation. Audience Computer and artificial intelligence scientists, information and communication technology specialists, and engineers in electronics and industrial manufacturing will find this book very useful.
Artificial Intelligence-The Driving Force of Industry 4.0 / Hesham Magd, Henry Jonathan, Shad Ahmad Khan, Mohamed El Geddawy -- Industry 4.0, Intelligent Manufacturing, Internet of Things, Cloud Computing / Sachi Pandey, Vijay Laxmi, Rajendra Prasad Mahapatra -- Artificial Intelligence of Things (AIoT) and Industry 4.0-Based Supply Chain (FMCG Industry) / Seyyed Esmaeil Najafi, Hamed Nozari, S A Edalatpanah -- Application of Artificial Intelligence in Forecasting the Demand for Supply Chains Considering Industry 4.0 / Alireza Goli, Amir-Mohammad Golmohammadi, S A Edalatpanah -- Integrating IoT and Deep Learning-The Driving Force of Industry 4.0 / Muhammad Farrukh Shahid, Tariq Jamil Saifullah Khanzada, Muhammad Hassan Tanveer -- A Systematic Review on Blockchain Security Technology and Big Data Employed in Cloud Environment / Mahendra Prasad Nath, Sushree Bibhuprada B Priyadarshini, Debahuti Mishra, Brojo Kishore Mishra -- Deep Learning Approach to Industrial Energy Sector and Energy Forecasting with Prophet / Yash Gupta, Shilpi Sharma, P Naveen Rajan, Nadia Mohamed Kunhi -- Application of Novel AI Mechanism for Minimizing Private Data Release in Cyber-Physical Systems / Manas Kumar Yogi, ASN Chakravarthy -- Environmental and Industrial Applications Using Internet of Things (IoT) / Manal Fawzy, Alaa El Din Mahmoud, Ahmed M Abdelfatah -- An Introduction to Security in Internet of Things (IoT) and Big Data / Sushree Bibhuprada B Priyadarshini, Suraj Kumar Dash, Amrit Sahani, Brojo Kishore Mishra, Mahendra Prasad Nath -- Potential, Scope, and Challenges of Industry 4.0 / Roshan Raman, Aayush Kumar -- Industry 4.0 and Manufacturing Techniques / Roshan Raman, Aditya Ranjan -- The Role of Multiagent System in Industry 4.0 / Jagjit Singh Dhatterwal, Kuldeep Singh Kaswan, Rudra Pratap Ojha -- An Overview of Enhancing Encryption Standards for Multimedia in Explainable Artificial Intelligence Using Residue Number Systems for Security / Akeem Femi Kadri, Micheal Olaolu Arowolo, Ayisat Wuraola Yusuf-Asaju, Kafayat Odunayo Tajudeen, Kazeem Alagbe Gbolagade -- Market Trends with Cryptocurrency Trading in Industry 4.0 / Varun Khemka, Sagar Bafna, Ayush Gupta, Somya Goyal, Vivek Kumar Verma -- Blockchain and Its Applications in Industry 4.0 / Ajay Sudhir Bale, Tarun Praveen Purohit, Muhammed Furqaan Hashim, Suyog Navale.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed January 4, 2023).
John Wiley and Sons
Keywords: Artificial intelligence -- Industrial applications; Industry 4.0.; Intelligence artificielle -- Applications industrielles; Industrie 4.0.; Artificial intelligence -- Industrial applications; Industry 4.0